PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BILINGUAL KELAS X POKOK BAHASAN GERAK LURUS DI SMA NEGERI 3 JAYAPURA - Yohanis, Joko; Triwiyono, .; Modouw, Wigaty (Jurnal Ilmu Pendidikan Indonesia, 2013)
This study is a Research and Development (R&D) which aims to develop bilingual physics module and determine the effectiveness of the use of the module in the learning process. The phase included preliminary study (define), program designing (design) and development (develop). There were two trials used to determine the effectiveness of the modules. The first is limited trial (pre-experimental) with design âone group pretest-posttest control designâ and the second is the extensive trial (quasi-experimental) using ânonequivalent group pretest-posttest designâ. The experiment was conducted SMAN 3 Jayapura for grade X, for limited trial uses only grade X1(33 student), while for extensive trial used two parallel classes i.e., grade X2 as experimental class (31 student) and grade X3 as control class (32 student). At the experimental class learning used the module and the control class learning did not use the module. N-gain analysis and t-test were used to know the effectiveness of the module use. N-gain at the experiment class is 0,72 while N-gain at control class is 0,47. The result shows that learning using the module is more effective than learning without using the module. Specialty of modules generated in this study have a complete and systematic structure, the discussion has focused coverage and scalable, have a sample in accordance to local approaches, and completely with a worksheet. In the implementation of the field still found weaknesses, those are lack of sample questions and a glossary of English for science. Keywords: development, module, and effectiveness.